Implicit Motives, Laterality, Sports Participation and Competition in Gymnasts - Schütz, Lisa-Marie; Schultheiss, Oliver C. (Frontiers in Psychology, 2020)
The implicit motivational needs for power, achievement, and affiliation are highly relevant in the context of sports. Sport enables people to experience achievement incentives like mastering challenges as well as social incentives such as recognition by teammates. Further, McClelland’s (1986) hypothesized that implicit motives are particularly associated right-hemisphere functions. Therefore, this preregistered study, conducted online, examines motivational needs using a standard picture-story exercise (PSE) and their associations with indicators of laterality, sports participation, and competition in gymnasts (N = 67). Further it explores how implicit motives interact with suitable motivational incentives in the prediction of sports performance. Results partly confirm a link between indictors of cerebral rightward laterality and implicit motives, showing that the implicit affiliation and achievement motives are positively associated with an indicator of emotional-perceptional laterality (chimeric-faces task), but not with an indicator of motor laterality (turning bias). Moreover, the implicit achievement motive was positively correlated with training hours. The implicit affiliation motive was negatively associated with competition level. The presence of achievement incentives (perceived control, failure) and affiliation incentives (training together or alone) did not interact with corresponding motives to predict sports performance.